Millennials and Reduced Car Ownership: Evidence from Recent Transport Surveys - Peng Chen; Haoyun Wang (Findings)
This study examines the likelihood millennials are to own a car and the factors that have driven a reduction in car consumption. Based on a travel decision survey performed in 2015 in San Francisco, no significant evidence supports the claim that millennials are different from prior generations in terms of car ownership. Individuals with higher incomes and those that preferred more access and convenience were more likely to own a vehicle.